Uterine arteriovenous malformation or uterine artery pseudoaneurysm secondary to uterine aspiration in cesarean scar ectopic pregnancy: a case report and review of the literature - Ngoc Diep Le; Phuc Nhon Nguyen (Journal of Medical Case Reports)
Abstract Introduction Uterine arteriovenous malformation or uterine artery pseudoaneurysm after the treatment of cesarean scar ectopic pregnancy is a scarce entity, leading to potentially life-threatening conditions due to the massive bleeding. The management remains significantly crucial. Herein, we report an uncommon case with surgical management of such a rare condition at our center. Presentation case A 31-year-old Vietnamese female patient (gravida 2, para 1) was hospitalized for cesarean scar pregnancy. The uterine aspiration was well performed. However, the woman was readmitted for an abnormally persistent hypervascularity at the site of cesarean scar ectopic pregnancy under repeated ultrasound scans. After counseling, arteriovenous malformation was suspected more, whereas uterine pseudoaneurysm was incompletely ruled out. Initially, gonadotropin-releasing hormone agonist was administered, with two doses of 37.5 mg. Later, the patient underwent laparoscopic intervention to suture the vascular proliferation mass to prevent spontaneous rupture. The surgery was achieved successfully. One more dose of gonadotropin-releasing hormone agonist was added. The ultrasound detected no existing lesion compared with previous ultrasonic imaging and serum beta-human chorionic gonadotropin declined to a negative value. The patient was monitored in 1 month uneventfully. Conclusion A high index of suspicion of uterine arteriovenous malformation or uterine artery pseudoaneurysm should be raised after uterine curettage of cesarean scar ectopic pregnancy. Ultrasound scan is still a pivotal first-line tool in assessing this abnormality. Laparoscopic surgery with compressing suture of the enhanced myometrial vascularity/arteriovenous malformation combined with administration of gonadotropin-releasing hormone agonist may be applied. This surgical approach has not been reported before, which makes our case report unique. Further cases are required for this rare entity so as to ensure patient safety.